2014
DOI: 10.1111/all.12354
|View full text |Cite
|
Sign up to set email alerts
|

Rhinitis is associated with a greater risk of intermittent claudication in adults

Abstract: Our findings suggest that rhinitis is associated with PAD, a predictor of future cerebrovascular and cardiovascular events, independently of the presence of atopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
(39 reference statements)
0
7
0
Order By: Relevance
“…13 In a recent retrospective cohort study, Chung et al 14 found in Taiwan that patients with asthma were at a 1.66-fold greater hazard to develop an acute coronary syndrome than those without the asthma history ( P  < 0.001). Ferrari et al 15 found patients with asthma are at higher risk of intermittent claudication, but not reach statistical significance. In the present study, we provide a relative “real world” scenario wherein the diagnosis of asthma and PAD are due to actual medical consultations.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…13 In a recent retrospective cohort study, Chung et al 14 found in Taiwan that patients with asthma were at a 1.66-fold greater hazard to develop an acute coronary syndrome than those without the asthma history ( P  < 0.001). Ferrari et al 15 found patients with asthma are at higher risk of intermittent claudication, but not reach statistical significance. In the present study, we provide a relative “real world” scenario wherein the diagnosis of asthma and PAD are due to actual medical consultations.…”
Section: Discussionmentioning
confidence: 95%
“…14 A recent multicase-control study showed asthmatic patients with rhinitis were at higher risk of intermittent claudication, but not significant. 15 However, the association between asthma and PAD has been less investigated.…”
Section: Introductionmentioning
confidence: 99%
“…. Rhinitis was associated with peripheral arterial disease, a predictor of future cerebrovascular and cardiovascular events, independent of the presence of atopy .…”
Section: Risk Factors For Ar and Allergen Sensitizationmentioning
confidence: 86%
“…Apart from the unlikely possibility that this association is due to chance, there are at least two plausible interpretations [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Ferrari et al [3] instead have shown that patients with rhinitis, regardless of the presence of atopy, have a higher risk of suffering from intermittent claudication [2].…”
Section: Introductionmentioning
confidence: 99%